Theories of Social Innovation - Logue, Danielle (Edward Elgar, 2019)
As we grapple with how to respond to some of the world’s most pressing problems, such as inequality, poverty and climate change, there is growing global interest in ‘social innovation’ as a potential solution. But what exactly is ‘social innovation’? This book describes three ways to theorise social innovation when seeking to manage and organize for both social and economic progress.
Keywords: Australie; Histoire; Innovation sociale; Théorie Néo-Institutionnelle